USE OF TAXONOMIC ANALYSIS IN ASSESSING BANK LIQUIDITY - Kubakh, Tetiana; Koilo, Viktoriia; Efimenko, Alyona (Socio-economic relations in the digital society, 2023)
Given the military actions that increase economic and financial threats in Ukraine, one of the main tasks for ensuring the stable functioning of the banking system is to ensure the liquidity of the bank. Successful implementation of this issue depends on an efficient, systematic, comprehensive assessment of liquidity indicators in order to make effective management decisions to balance the bank's assets and liabilities by terms and amounts. The world practice has developed a powerful toolkit for assessing bank liquidity, while the challenges of today require diversification of approaches to addressing this issue.The purpose of the article is to define the theoretical essence and practical component of bank liquidity, which makes it possible to more thoroughly determine the areas of analysis and evaluation, as well as to apply taxonomic analysis to determine the level of bank liquidity.Based on the study of scientific approaches, the author has formed her own interpretation of the category of "bank liquidity". It is proposed to analyze and evaluate the bank's liquidity on the basis of the formed system of indicators, which includes regulatory indicators from the regulator. The state of liquidity of the banking system of Ukraine is studied, which allows a comprehensive assessment of the factors influencing the liquidity of a bank as a structural element. On the example of JSC CB Raiffeisen Bank, the liquidity analysis was carried out using a system of indicators, and shortcomings in the bank's work were identified. For a more in-depth study on the example of the bank, a taxonomic analysis was carried out to determine the level of liquidity of JSC CB "Raiffeisen Bank".Based on the analysis and assessment of the liquidity of the systemically important bank and the domestic banking system, a surplus was identified. This trend is not positive for the potential development of Ukraine's economy and also reduces the level of profit in the context of a single bank. The taxonomic analysis makes it possible to further predict the development of the integral liquidity indicator, which contributes to the formation of an effective management policy.
Keywords: bank liquidity; banking system liquidity; taxonomic analysis of liquidity